IMPORTANCE OF PHYSICAL ACTIVITY IN PEOPLE WITH MULTIPLE SCLEROSIS - Una; Tomanovic Vujadinovic, Sanja; Krstic, Nevena; Ilic, Nela (Medical Research, 2025)
Physical activity (PA) in people with multiple sclerosis (pwMS) is related to positive effects on numerous bodily functions such as mobility, balance, fatigue, cognition and improves their overall quality of life. Recent research pointed out possible effects of PA on disease progression and even on the risk of developing the disease. Despite these facts, pwMS are still less active than general sedentary population, so improving their participation in PA should be one of the very important goals in their treatment. In order to adequately tailor PA goals, pwMS should be referred to rehabilitation specialist from the initial stage of the disease. It appears that programs that include walking are much appreciated by pwMS, so perhaps they should be prioritized in all patients with mild and moderate disability levels. Special attention is needed for the group of patients with severe disability in order to improve availability of venues and trained assistants that can help them stay maximally active. Barriers to reduced PA stem from the patient’s health status, cognitive and behavioral factors on one hand, and the physical and social environment on the other. For that reason, it is very important to include patient’s preference for a modality of PA when proposing PA plans. Long-term adherence to PA programs remains insufficiently studied, so further research is needed to address this important issue, which appears to be a key step toward improving PA engagement in pwMS.